3D printing of bioinspired hydrogel microstructures with programmable and complex shape deformations based on a digital micro-mirror device. (January 2023) - Yang, Wenguang; Wang, Zhen; Wang, Xiaowen; Yu, Tao; Xie, Shuangxi; Ge, Zhixing
Highlights: A programmable control of single-material hydrogel deformation stimulated by unilateral water absorption is proposed. Various bionic deformation structures such as flower folding are fabricated. A water-absorbing and swelling powered micro-manipulator is fabricated to achieve controlled grasping and releasing of objects. Abstract: 4D printing, which enables programmable deformation of structures, has broadened the application of 3D printing. Nowadays, 4D printing is usually done by multi-material printing, in which different spatial locations are endowed with different properties. This approach, however, increases the difficulty of 3D printing. Here, we propose a programmable control of single-material hydrogel deformation stimulated by unilateral water absorption. The control scheme includes structure control, gray value control, droplet distribution control, and hydrogel concentration control. Various bionic deformation structures are fabricated. Furthermore, a water-absorbing and swelling powered micro-manipulator is fabricated to achieve controlled grasping and releasing of objects. The materials and stimulation modalities in the proposed programmable control scheme have good cytocompatibility and are easily accessible. This suggests that the control scheme holds great potential for applications in tissue engineering, bionic technology, and micro and nano fabrication.